The Labor Market Integration of Refugee Migrants in High-Income Countries - Courtney Brell; Christian Dustmann; Ian Preston (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2020)
We provide an overview of the integration of refugees into the labor markets of a number of high-income countries. Discussing the ways in which refugees and economic migrants are differently selected and so might be expected to perform differently in a host country's labor market, we examine employment and wages for these groups over time after arrival. There is significant heterogeneity between host countries, but in general refugees experience persistently worse outcomes than other migrants. While the gaps between the groups can be seen to decrease on a timescale of a decade or two, this is more pronounced in employment rates than it is in wages. We also discuss how refugees are distinct in terms of other factors affecting integration, including health, language skills and social networks. We provide a discussion of insights for public policy in receiving countries, concluding that supporting refugees in early labor market attachment is crucial.
Keywords: 330